Strategic Intelligence Analysis in Early Detection of Potential Food Crimes in West Java - Wiku Kalis; Arthur Josias Simon Runturambi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In West Java, which is one of the food barns In Indonesia, crime in the food sector is a separate problem that hinders the realization of food security. The West Java Police, especially the Intelkam Directorate, has an obligation to carry out early detection of potential food crimes. This study uses a qualitative approach. The results of the study are: (1) In West Java, throughout 2020 there were 7 cases recorded with 12 suspects. Meanwhile, throughout 2021 from January to September there was 1 case with 2 suspects. The drastic reduction in food crime in West Java is due to the West Java Police through the Intelkam Directorate carrying out early detection activities and preventive measures to suppress food crime, namely as many as 23 activities consisting of counseling, monitoring prices through market operations, coordinating with stakeholders, and various other activities. (2) The potential for food crime in West Java is analyzed through Strategic Intelligence Applications Down McDowell.